Glandular odontogenic cyst mimicking central mucoepidermoid carcinoma - Prabhu, Sudeendra (Medknow Publications, 2010)
Glandular odontogenic cyst (GOC) is a rare developmental cyst of the jaws. The most common site of occurrence is the anterior mandible, and it is most commonly seen in middle-aged people. It is a destructive lesion with a high rate of recurrence. A predilection for men is observed. Clinical and radiographic findings are not specific, and it can mimic as any other destructive lesion of the jaw. The histopathological features of GOC and those of low-grade central mucoepidermoid carcinoma (MEC) are similar. Often, they are misdiagnosed as MEC. We present a case of GOC in the posterior maxilla, which is a rare site. The similarities and differences between GOC and central MEC are also discussed.